Succession intention and environmental investment: The moderating role of social status - Zhang, Qi; Xiong, Lei; Yan, Youliang; Song, Zengji; Wen, Zezhou (Frontiers in Psychology, 2022)
Drawing on expectancy theory, this study explains how founders’ succession intentions might influence family firms’ environmental environments. Using a nationally representative sample of Chinese private firms, we find that family firms make more environmental investments when founders have succession intentions. We also find that the relationship between founders’ succession intentions and family firms’ environmental investments is negatively moderated by the founders’ subjective social status. Moreover, the results show that, compared with ownership succession intentions, the positive role of founders’ management succession intentions on family firms’ environmental investments is more prominent. This study helps us to better understand the impact of succession intentions on family business decision-making from a psychological perspective. It enriches the research on succession intentions and provides practical implications for family firms’ sustainable development.